Penerapan Ajaran Turut Serta dalam Pertanggungjawaban Pelaku Tindak Pidana Narkotika - Matheos Bastian Wattimena; Elsa Rina Maya Toule; Julianus Edwin Latupeirissa (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Narcotics abuse is the use of narcotics not for medicinal purposes, which causes changes in physical and psychological functions and causes dependence without a prescription and without the supervision of a doctor. Meanwhile, narcotics illicit trafficking is any activity or series of activities carried out without rights or against the law which is determined as a narcotics crime.Purposes of the Research: This writing aims to apply the teachings of participating in decisions in the Masohi District Court Decision. Methods of the Research: The type of legal research carried out is normative juridical, with sources of legal material in the form of primary and secondary legal materials. The problem approach is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials is done by first collecting primary legal materials and then linking them to secondary legal materials. The processing and analysis of legal materials is described qualitatively.Results of the Research: Narcotics abuse is the use of Narcotics for no purpose, which causes changes in function and psychological treatment and causes physical dependence without a prescription and without a doctor's supervision. Meanwhile, illicit drug trafficking is any activity or desire carried out without rights or against the law which is determined as a narcotics crime. One example of a case based on the decision of the Masohi District Court Number 12/Pid.Sus/2020/PN Msh and Number 12/Pid.Sus/2020/PN Msh carried out by the two defendants named Trikarna Lewenussa Alias Cetril and Rosihan Anwar Sahulau Alias Andri.